International Monetary Cooperation Under Tariff Threats - Flavio Delbono; Vincenzo Denicolò; Giorgio Basevi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1988)
We analyze games between two countries that use the tariff as a threat to induce each other to follow monetary policies equivalent to those that would obtain under a cooperative game. The analysis shows that under certain assumptions concerning the shares of tariff revenues that the countries spend on imports, the punishment structure, and the discount factors, the outcome of the games converges to a monetary policies. It is suggested that the model could be applaied to current relations between the US, Germany and Japan.
Keywords: 330